ANALISIS PROMINENSI UJARAN PRESIDEN JOKOWI TERHADAP KONFLIK PALESTINA – ISRAEL: KAJIAN FONETIK AKUSTIK - Ayuanda, Winda; Syarfina, Tengku; Gustianingsih, Gustianingsih; Muskar, Rahlina; Erwina, Emmy (MEDIASI Jurnal Kajian dan Terapan Media, Bahasa, Komunikasi, 2024)
The aim of this research is to represent the prominence contained in President Jokowi's statements regarding the Palestinian and Israeli conflicts, as well as to find the values of frequency, duration, and intensity as characteristics of the sound. This research is quantitave research with an instrumental approach. The research data is an audiovisual form, and it is analyzed using the Praat application. The result shows that the prominence of President Jokowi's statement is found in the words 'indonesia' and 'war', namely in the rightmost syllables: -sia and -rang. When communicating, speakers tend to pay more attention to words that they think are important.  It has also been proven that the factors that influence the formation of prominence are pitch, loudness, and duration, with values of F0, intensity, and duration for stressed syllables is higher than unstressed syllables. Apart from that, prominence can also occur when speakers want to highlight words that are considered important.